2020
DOI: 10.1002/ccr3.3621
|View full text |Cite
|
Sign up to set email alerts
|

The clinical course and management of cervical cancer with splenic metastasis: Case report and review of the literature

Abstract: Adenovirus‐mediated herpes simplex virus thymidine kinase gene therapy (ADV‐TK) in combination with interventional treatment could relieve the symptoms in patients with widespread splenic metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 15 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Sixty percent of the cases were metastases from gynecological carcinomas, with the majority being ovarian and endometrial cancer as the primary tumors [ 19 ]. The most recent review published in 2020 found a total of eight cases of solitary splenic metastasis from cervical cancer in the literature where two of them were AC and the rest were SCC [ 10 ]. This could be explained by the higher prevalence of SCC compared to AC [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixty percent of the cases were metastases from gynecological carcinomas, with the majority being ovarian and endometrial cancer as the primary tumors [ 19 ]. The most recent review published in 2020 found a total of eight cases of solitary splenic metastasis from cervical cancer in the literature where two of them were AC and the rest were SCC [ 10 ]. This could be explained by the higher prevalence of SCC compared to AC [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case the patient had complete radiological and pathological response after treatment with chemotherapy followed by brachytherapy, but she developed splenic oligometastasis afterwards. With regards to cervical cancer splenic metastasis, surgical intervention by splenectomy is the definitive treatment in case of solitary splenic metastasis [ 9 , 10 , 12 ]. However, many authors recommend adjuvant chemotherapy in isolated splenic metastasis as it is considered a form of distant metastases [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations